NON-DESTRUCTIVE TESTING AND QUALITY OF ENGINEERING PRODUCTS QUALITY - Povgorodniy, Volodymyr; Babnyak, Oleksandr (Problems of Friction and Wear, 2026)
The article considers the types of non-destructive testing, fatigue failure, quality and effectiveness of non-destructive testing methods. It is indicated that the most complete detection of defects is provided, as a rule, when using several methods. Complex systems of non-destructive testing, consisting of several physical methods, are usually used when the ability to detect defects using individual methods (i.e., type, size, location) is different, unequal. The effectiveness of decisions made when designing various industrial equipment depends on the reliability of knowledge about thermophysical processes during its operation. The methods of modeling and identification of heat transfer processes can be based on solutions of inverse problems of thermal conductivity (TC) and thermoelasticity (TCT). In some cases, determining the thermophysical characteristics (TPC) of a material or heat transfer parameters by the TCT method is practically the only way to obtain the necessary information about the object under study. The main principles of methodological recommendations for determining the economic efficiency of NC are the approach to determining the effect and the formation of a single methodological approach to determining the efficiency of NC both during manufacture and operation. With the help of NC, information can be obtained about individual product properties, that is, about individual unit quality indicators. The development and widespread use of NC methods led to the development of applied qualimetry and the theory of inverse problems.